6 Documents Relative To The Colonial History Of The State Of New-York 316 (1855) - (:unkn) unknown (My University, 1744)
forbid the exportation of gunpowder
Keywords: TRANSFER; TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER